Micro/nanoscale pore structure and fractal characteristics of tight gas sandstone: A case study from the Yuanba area, northeast Sichuan Basin, China. (December 2018) - Zhu, Feng; Hu, Wenxuan; Cao, Jian; Sun, Funing; Liu, Yifeng; Sun, Zhenmeng
Abstract: The pore size distribution (PSD) and fractal dimension are two typical parameters that are used to evaluate the heterogeneous characteristics of unconventional reservoir pores. The micro/nanoscale PSD and pore fractal-dimension characteristics of tight gas sandstones from the Upper Triassic Xujiahe formation in the Yuanba area were investigated by using nuclear magnetic resonance (NMR), nuclear magnetic resonance cryoporometry (NMRC), mercury injection capillary pressure (MICP) and scanning electronic microscopy (SEM) techniques. To date, no other attempts have been made to use NMRC with octamethylcyclotetrasiloxane (OMCTS) as a probe material to describe the pore fractal characteristics of tight gas sandstones. In this study, the fractal dimensions of tight gas sandstones were estimated by processing raw NMRC data with a fractal theoretical model, and the NMRC fractal results were compared to the calculated fractals from the MICP tube model, MICP sphere model and NMR T2 spectrum. The results consistently show that the pore fractal characteristics of tight sandstone samples from the Yuanba area exhibit multiple fractal structures at different pore-size ranges; large pores in the samples are more complex with rougher surfaces, and small pores correspond to smoother surfaces. Sandstones with greater porosity and pore space possess more heterogeneous structures. The PSD and fractal dimensions can be combined and used as an indicator for the presence of gas-bearing and dry formations in the study area. The tight sandstone samples from the dry formations have both lower porosities and smoother pore surfaces with smaller fractal dimensions; these characteristics may not be beneficial for the preservation of hydrocarbon fluids in the target area. Highlights: NMRC with OMCTS as probe to describe sandstone pore fractal dimensions was proposed. Characteristics of tight sandstones pore structure were studied. The different fractal dimensions result from different methods were discussed.